PENGUNAAN TIGA JENIS DAGING TERHADAP NILAI KANDUNGAN LEMAK, PROTEIN DAN ORGANOLEPTIK ILABULO - Siswatiana Taha; Nibras Karnain Laya (xxxx-xxxx, 2022)
This study aims to analyze the level of preference and nutritional value of ilabulo with different filling ingredients. This study used a completely randomized design (CRD) consisting of 3 treatments and 4 replications. The research treatments were P1 (100 grams of chicken meat), P2 (100 grams of beef), P3 (100 grams of mutton). The parameters observed were the sensory value and the fat and protein content of the ilabulo. The highest fat content in this study was beef ilabulo (8.33%), chicken meat ilabulo (6.15%) while the value of mutton ilabulo (4.49%). As for the protein content in each ilabulo, namely chicken meat ilabulo (18.21%), beef ilabulo (16.65%), mutton ilabulo (13.80%). The organoleptic value of the texture of the ilabulo with different meat, namely chicken meat ilabulo. The analysis showed that the ilabulo with different meat ingredients varied the texture of the ilabulo, as well as the color where mutton ilabulo had a blackish gray color compared to chicken and beef ilabulo. The panelists preferred the aroma of chicken meat ilabulo to beef ilabulo and mutton ilabulo. Beef ilabulo has a higher elasticity value than chicken meat ilabulo and mutton ilabulo. As for the taste of ilabulo from this treatment, panelists are more interested in chicken meat ilabulo because it has a distinctive taste than beef ilabulo and mutton ilabulo.Keywords: Ilabulo, Chicken, Beef, Mutton, Fat, Protein, Organoleptics